(3JaSjQ HYV BjGJ ef GdbQGf GdcQjes - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B( (3dGLfGM Ydjce Gf WdbJe GdfSGA eGde JeShgf (B) s
(3BNQgG (B:s
(3jfJgi CKfGA JaSjQg dShQI GdYfcHhJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B302s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs